Genomic and antigenic diversity of colonizing Klebsiella pneumoniae isolates mirrors that of invasive isolates in Blantyre, Malawi. Issue 3 (18th March 2022) - Lewis, Joseph M.; Mphasa, Madalitso; Banda, Rachel; Beale, Mathew A.; Mallewa, Jane; Heinz, Eva; Thomson, Nicholas R.; Feasey, Nicholas A.
Abstract : Members of the Klebsiella pneumoniae species complex, particularly K. pneumoniae subsp. pneumoniae are antimicrobial resistance (AMR) associated pathogens of global importance, and polyvalent vaccines targeting Klebsiella O-antigens are in development. Whole-genome sequencing has provided insight into O-antigen distribution in the K. pneumoniae species complex, as well as population structure and virulence determinants, but genomes from sub-Saharan Africa are underrepresented in global sequencing efforts. We therefore carried out a genomic analysis of extended-spectrum beta-lactamase (ESBL)-producing K. pneumoniae species complex isolates colonizing adults in Blantyre, Malawi. We placed these isolates in a global genomic context, and compared colonizing to invasive isolates from the main public hospital in Blantyre. In total, 203 isolates from stool and rectal swabs from adults were whole-genome sequenced and compared to a publicly available multicounty collection and previously sequenced Malawian and Kenyan isolates from blood or sterile sites. We inferred phylogenetic relationships and analysed the diversity of genetic loci linked to AMR, virulence, capsule and LPS O-antigen (O-types). We find that the diversity of Malawian K. pneumoniae subsp. pneumoniae isolates represents the species' population structure, but shows distinct local signatures concerning clonal expansions. Siderophore and hypermucoidy genes were more frequent in invasive versus colonizing isolates (present in 13 % vs 1 %) but still generally lacking in most invasive isolates. O-antigen population structure and distribution was similar in invasive and colonizing isolates, with O4 more common (14%) than in previously published studies (2–5 %). We conclude that host factors, pathogen opportunity or alternate virulence loci not linked to invasive disease elsewhere are likely to be the major determinants of invasive disease in Malawi. Distinct ST and O-type distributions in Malawi highlight the need to sample locations where the burden of invasive Klebsiella disease is greatest to robustly define secular trends in Klebsiella diversity to assist in the development of a useful vaccine. Colonizing and invasive isolates in Blantyre are similar, hence O-typing of colonizing Klebsiella isolates may be a rapid and cost-effective approach to describe global diversity and guide vaccine development.